Penanganan herpes simpleks labialis rekuren (Management of recurrent herpes simplex labialis) - Harlina Harlina; Erni Marlina; Athifah Athifah (DiscoverSys Inc., 2014)
Infections of Herpes simplex virus 1 (HSV-1), is a viral infection that is often in the form of primary gingivostomatitis.Its mild form usually provides subclinical symptoms that are not clear. Herpes virus transmission can occur throughcontact with secretions from the mouth mucocutaneous and patient’s genital. It is reported that a 10 years-old malepatient complaining of pain in the left corner of the lip and lower lip mucosa experienced since three days ago. Sevendays ago there was a similar injury in the right corner of his mouth. This condition was often experienced the patient.As its management of HSV-1, the patient was given acyclovir, paracetamol and vitamin B complex. After 7 days thepatient was declared healed. It is concluded that treatment for HSV-1 infected patients include causative treatmenttogether with analgesic and antipyretic. Patients are also prouded with supporting treatments, such as high-caloriand-proteindilutedfood,multivitamins,andanastheticummouthwasher.